THE DESIGN OF A MODULAR WIND TURBINE MEANT FOR HOUSES AND OFFICE BUILDINGS - RĂDUICĂ Felix (Journal of Industrial Design and Engineering Graphics, 2016)
This paper describes a new wind turbine design which can be implemented for home, office and public buildings. Also, this article presents specific steps taken by the designer to develop the product. A honeycomb design has been implemented for modularity reasons. Certain measures have been taken to ensure the quality of the design including, but not limited to: an emphasis on design principles, product development and shapes described by and found in nature.